An emotion assessment model for Elementary School students - Herwin Herwin; Djemari Mardapi (Graduate School, Universitas Negeri Yogyakarta, 2017)
This study aims to produce an emotion assessment model for elementary school students, identify the characteristics of the quality of the emotion assessment instrument, and obtain information about the results of emotion assessment. The study employed the design and development (DD) approach. The study was conducted at 9 elementary schools. The data were collected through questionnaires, observations, and interviews. The data analysis techniques were Cohen’s Kappa Inter-Rater analysis and Goodness of Fit analysis using Mokken Scalability Analysis. The results of the study show that the emotion assessment model for students consists of six aspects of emotion, i.e.: fear, anger, sadness, boredom, joy, and curiosity. The model consists of 16 indicators and 60 observed items. The emotion assessment model consists of instrument grids, a user’s guide, a scoring rubric, and a guide for result interpretation. The emotion assessment model is valid and reliable based on the in inter-rater testing through Cohen’s Kappa statistics with an average Kappa coefficient of 0.82 (almost perfect). The results of emotion assessment by teachers are: the fear of elementary school students ranging from high, medium and low category. The anger of students ranges from high, medium and low. The sadness of students ranges from moderate to low category. Boredom of students ranges from medium to low category. The joy of the students is in the high category. The curiosity of students ranges from high and medium category.